2008
DOI: 10.1007/s10474-007-7129-8
|View full text |Cite
|
Sign up to set email alerts
|

The lattice point discrepancy of a torus in ℝ3

Abstract: This article provides an asymptotic formula for the number of integer points in the three-dimensional body   x y z   = t   (a + r cos α) cos β (a + r cos α) sin β r sin α   , 0 α, β < 2π, 0 r b,for xed a > b > 0 and large t.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…A particularly symmetric example, considered in [Now08a], is the solid torus (1.1) T = (x, y, z) ∈ R 3 : ρ ′ − x 2 + y 2 2 + z 2 ≤ ρ 2 where 0 < ρ < ρ ′ are fixed constants. Its volume is 2π 2 ρ 2 ρ ′ but the natural main term to approximate the number of lattice points in the R-scaled torus…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A particularly symmetric example, considered in [Now08a], is the solid torus (1.1) T = (x, y, z) ∈ R 3 : ρ ′ − x 2 + y 2 2 + z 2 ≤ ρ 2 where 0 < ρ < ρ ′ are fixed constants. Its volume is 2π 2 ρ 2 ρ ′ but the natural main term to approximate the number of lattice points in the R-scaled torus…”
Section: Introductionmentioning
confidence: 99%
“…Nowak [Now08a] who obtained E(R) = O R 11/8+ǫ . He wrote M(R) as a series depending on elementary functions but it is equivalent to our statement after substituting the asymptotic formula for J 1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the remainder, it has been shown by D. Popov [13] that Δ T (t) t 3 2 − 1 286 +ε , and by the second named author [12] that Δ T (t) t 3 2 − 1 8 +ε . It is the objective of this paper to show that again Δ T (t) t 1+ε in meansquare.…”
Section: Introductionmentioning
confidence: 99%
“…
For positive constants a > b > 0, let PT (t) denote the lattice point discrepancy of the body tT a,b , where t is a large real parameter and T = T a,b is bounded by the surfaceIn a previous paper [12] it has been proved thatwhere F a,b (t) is an explicit continuous periodic function, and the remainder satisfies the ("pointwise") estimate Δ T (t) t 11/8+ε . Here it will be shown that this error term is only t 1+ε in mean-square, i.e., that

for any ε > 0.

…”
mentioning
confidence: 99%